Biomechanics of the Wrist Joint - An, Kai-Nan; Berger, Richard A.; Cooney, William P. (Springer New York, 1991)
Clinical interest in the wrist joint has accelerated markedly in the last two decades. Clinical diagnosis based on a greater understanding of wrist anatomy, biomechanics and increasingly sophisticated imaging techniques has markedly enhanced our ability to treat disorders of this joint. As our clinical acumen becomes better, we increasingly need more accurate understanding of the basic mechanisms by which the wrist is able to carry out its function. This book represents a compendium of work done by a number of authors in the basic sciences and their presentations at a recent workshop on biomechanics. This work, while at the forefront of current research in this area, is but an indicator of the type of information that is increasingly required to progress in this field. The authors have made some sound contributions and this book should be of considerable interest and help to those individuals who are contributing to progress in this field. It will be of even greater importance if it helps to stimulate the reader to become involved in further research into the intricacies of the wrist and help us to solve its numerous problems. I hope the reader will enjoy reading these chapters as much as I did in listening to them at the time of their presentations. Ronald L. Linscheid, M.D. President 1989-1990 American Society for Surgery of the Hand Mayo Clinic Rochester, Minnesota Preface Work related injury lIas become a major factor in current world economics